COMPREHENSIVE METHODS OF PHYSICAL THERAPY FOR CHILDREN WITH CEREBRAL PALSY - Horoshko, V. I.; Zhamardiy, V. O.; Litvinov, P. Yu. (Rehabilitation and Recreation, 2025)
Purpose. This study aims to characterize modern technologies in the diagnosis and rehabilitation of children with cerebral palsy, to determine the main methods of physical therapy for this pathology. The aim of the scientific study is to assess the effectiveness of comprehensive physical therapy methods for children with cerebral palsy in improving their quality of life and motor functions. Material. To achieve the goal, theoretical analysis and generalization of scientific and methodical literature materials, mathematical and statistical processing of research data, study of medical card data, and observations were carried out. Findings. During the research, we discovered that modern scientists emphasize the theoretical and methodological aspects of physical therapy of children with cerebral palsy using standard (therapeutic gymnastics, therapeutic massage, etc.) and modern methods of physical therapy (Vojta therapy, Bobat therapy, hippotherapy, etc.). Many researchers believe that choosing an effective method of developing children’s everyday independence, self-care, improving motor activity, forming basic motor skills, developing basic physical fitness and ensuring communication is a problem. The variety of forms and clinical manifestations of childhood cerebral palsy requires a differentiated approach to the selection and application of modern methods of physical therapy. A complex combination of physical therapy methods in the restorative treatment of children with this disease gives much higher results and helps to restore motor functions faster. Conclusions. Physical therapy of children with cerebral palsy should be used at all stages of treatment. Also important is the cause, form, stage and degree of development of cerebral palsy, as well as possible complications. The study confirms the importance of an individual and comprehensive approach to physical therapy for children with cerebral palsy. The results demonstrate that a combination of different physical therapy methods can significantly improve motor function, coordination, and overall development in children with cerebral palsy.